2022
DOI: 10.1002/htj.22406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of receiver geometry on the optical and thermal performance of a parabolic trough collector

Abstract: In this study, the optical and thermal performance of a Parabolic Trough Collector PTC system is investigated theoretically. A series of numerical simulations and theoretical analysis has been conducted to investigate the effect of the receiver geometry and location relative to the focal line on its optical performance. The examined receiver geometries are circular, square, triangular, elliptical and a new design of circular-square named as channel receiver.The thermal performance of PTC is studied for differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…They discovered that improving tube thickness up to a certain level improves the PTC system's performance. Al-Dulaimi et al [4] have estimated the efficiency of five different shapes of receiver tubes through numerical simulations and theoretical analysis. They concluded that the efficiency of tested receiver shapes could be represented in the following order.…”
Section: Introductionmentioning
confidence: 99%
“…They discovered that improving tube thickness up to a certain level improves the PTC system's performance. Al-Dulaimi et al [4] have estimated the efficiency of five different shapes of receiver tubes through numerical simulations and theoretical analysis. They concluded that the efficiency of tested receiver shapes could be represented in the following order.…”
Section: Introductionmentioning
confidence: 99%